Oxytocin receptor single nucleotide polymorphism predicts atony-related postpartum hemorrhage - Erickson, Elise N.; Krol, Kathleen M.; Perkeybile, Allison M.; Connelly, Jessica J.; Myatt, Leslie (BMC pregnancy and childbirth, 2022)
Background Postpartum hemorrhage remains a key contributor to overall maternal morbidity in the United States. Current clinical assessment methods used to predict postpartum hemorrhage are unable to prospectively identify about 40% of hemorrhage cases. Oxytocin is a first-line pharmaceutical for preventing and treating postpartum hemorrhage, which acts through oxytocin receptors on uterine myocytes. Existing research indicates that oxytocin function is subject to variation, influenced in part by differences in the DNA sequence within the oxytocin receptor gene. One variant, rs53576, has been shown to be associated with variable responses to exogenous oxytocin when administered during psychological research studies. How this variant may influence myometrial oxytocin response in the setting of third stage labor has not been studied. We tested for differences in the frequency of the oxytocin receptor genotype at rs53576 in relationship to the severity of blood loss among a sample of individuals who experienced vaginal birth. Methods A case–control prospective design was used to enroll 119 postpartum participants who underwent vaginal birth who were at least 37 weeks of gestation. Cases were defined by either a 1000 mL or greater blood loss or instances of heavier bleeding where parturients were given additional uterotonic treatment due to uterine atony. Controls were matched to cases on primiparity and labor induction status. Genotype was measured from a maternal blood sample obtained during the 2 nd postpartum month from 95 participants. Statistical analysis included bivariate tests and generalized linear and Poisson regression modeling. Results The distribution of the genotype across the sample of 95 participants was 40% GG ( n = 38), 50.5% AG ( n = 48) and 9.5% AA ( n = 9). Blood loss of 1000 mL or greater occurred at a rate of 7.9% for GG, 12.5% for AG and 55.6% for AA participants ( p = 0.005). Multivariable models demonstrated A-carriers (versus GG) had 275.2 mL higher blood loss (95% CI 96.9–453.4, p < 0.01) controlling for parity, intrapartum oxytocin, self-reported ancestry, active management of third stage or genital tract lacerations. Furthermore, A-carrier individuals had a 79% higher risk for needing at least one second-line treatment (RR = 1.79, 95% CI = 1.08–2.95) controlling for covariates. Interaction models revealed that A-carriers who required no oxytocin for labor stimulation experienced 371.4 mL greater blood loss (95% CI 196.6–546.2 mL). Conclusions We provide evidence of a risk allele in the oxytocin receptor gene that may be involved in the development of postpartum hemorrhage among participants undergoing vaginal birth, particularly among those with fewer risk factors. The findings, if reproducible, could be useful in studying pharmacogenomic strategies for predicting, preventing or treating postpartum hemorrhage.